Mechanical properties of heat‐treated polypropylene separators for Lithium‐ion batteries. Issue 9 (12th July 2022) - Moghim, Mohammad Hadi; Nahvibayani, Ashkan; Eqra, Rahim
Abstract: Lithium‐ion battery separators act as components that have a function of thermal shutdown at a specific temperature for safety issues. Exposing these separators at high temperatures, lower than the shutdown temperature, can affect the performance, structure, and properties of these batteries. In this research, the effect of thermal shrinkage on the structural characterization, thermal and mechanical properties, and ionic conductivity of a polypropylene (PP) lithium‐ion battery separator was studied. The obtained results showed that the PP separator had not any thermal shrinkage along the transverse direction (TD) at different temperatures, but thermal shrinkage along the machine direction (MD) increased from 1.2% at 100°C to 45.9% at 160°C. Heat treatment of the PP separator above 150°C resulted in no air permeability, and the porosities being completely closed. The yield strength along TD was increased due to thermal shrinkage and this behavior enhanced with heat treatment temperature to about 280%. Tensile properties of the separator showed strain‐rate dependency along MD and TD. The puncture failure mode of puncture test was changed from a zigzag surface along TD (failure mode B) at the low heat treatment temperature to cracks along MD at the higher temperature. Finally, the ionic conductivity was decreased from 0.7409 mS.cm −1 for the untreated sample to 0.6881 mS.cm −1 for the heat‐treated PP separator at 130°C. Abstract : Different characteristics of heat‐treated PP separators for lithium‐ion batteries.